THE INFLUENCE OF THE LEADERSHIP STYLE OF THE CHAIRMAN OF THE DPRD OF TANGERANG CITY ON THE PERFORMANCE OF LEGISLATIVE ORGANIZATIONS IN THE COVID-19 ERA - W.A. William Yani; Muh. Kadarisman; Evi Satispi; Azhari Aziz Samudra (DIA: Jurnal Administrasi Publik, 2024)
The pandemic period where coordination activities were limited to online meetings because of the fear of interacting face-to-face in the coordination process with related parties. Research Methods using quantitative methods. In collecting data, the author uses a questionnaire as a data collection tool. And using multiple linear regression. The research location is in the DPRD of Tangerang City organization. Based on the results of the study 1) There is an influence of policies on handling the Covid-19 pandemic on the performance of the DPRD of Tangerang City Organization. The value of the policy coefficient for handling the Covid 19 pandemic is 0.259, which is positive with the result of t count of 2.934 > t table (1.679) and a significance of t of 0.005 <0.05. 2) The value of the leadership style coefficient of the DPRD of Tangerang City chairman is 0.456, which is positive with the results of t count of 7.885 > t table (1.679) and a significance of t of 0.000 <0.05. That is, H2 is accepted. 3) The calculated F value obtained is 48.965 > F table (3.20) and the F significance obtained from the model is 0.000 less than 0.05. That is, H3 is accepted. Based on the results of the study, it can be concluded that the Leadership Style Variable of the Chairperson of the DPRD of Tangerang City can contribute an influence of 0.456 which is stronger than the Covid-19 Pandemic Handling Policy variable which only contributes 0.259. This means that the leadership style of the DPRD of Tangerang City Chairman has a greater impact on increasing the DPRD of Tangerang City Organizational Performance in 2020-2021.